Adventures in Kate Bush and theory - Withers, Deborah M. (HammerOn Press, 2010)
Through in-depth readings of the often critically neglected works of Bush's career (The Kick Inside, Lionheart, The Dreaming, The Red Shoes and her film The Line, the Cross and the Curve), Withers guides the reader through the complexity of Bush's art and how it transformed popular culture.